Factor Contributing Length of Stay of COVID-19 Patients in Hospitals: Scoping Review - Nana Septiana Widayati; Titin Andri Wihastuti; Laily Yuliatun; K Kumboyono (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The very high transmission of COVID-19 has had a massive impact on the current health system, one of which is in hospitals. Understanding the length of stay for COVID-19 patients is needed in a pandemic because the demand for patient care in hospitals is increasing. This paper aims to understand the factors that can affect the length of stay of COVID-19 patients in the hospital. Searches were done on online databases at ScienceDirect, EBSCO, and Google Scholar. A systematic review was carried out on journals published in the last three years, namely 2019-2022, and in English, and met the inclusion and exclusion criteria that had been set. The search results found 12 articles that met the criteria and discussed various factors influencing the severity and length of hospital stay. Several factors identified as having an effect were comorbid, gender, smoking, gender, type of virus, severity, age, and laboratory finding. Hospital preparedness is needed to deal with fluctuations in COVID-19 patients and the number of requests for treatment facilities during the pandemic. Abstrak: Penularan COVID-19 yang sangat cepat menimbulkan dampak yang besar pada sistem kesehatan saat ini salah satunya di rumah sakit. Pemahaman mengenai lama perawatan di rumah sakit (length of stay) pada pasien COVID-19 sangat diperlukan dalam kondisi pandemi dikarenakan permintaan perawatan pasien di rumah sakit meningkat. Tujuan dari penulisan ini adalah untuk memahami faktor-faktor yang dapat berpengaruh pada lama rawat inap pasien COVID-19 di rumah sakit. Pencarian dilakukan pada database online di ScienceDirect, EBSCO dan Google Schoolar. Tinjauan sistematis dilakukan pada jurnal yang terbit pada 3 tahun terakhir yaitu tahun 2019-2022 dan berbahasa inggris serta memenuhi kriteria inklusi dan eksklusi yang telah ditetapkan. Hasil pencarian didapatkan 12 artikel yang memenuhi kriteria dan membahas berbagai faktor yang berpengaruh pada keparahan dan lama perawatan pasien di rumah sakit. Beberapa faktor yang diidentifikasi dapat berpengaruh adalah komorbid, jenis kelamin, merokok, jenis kelamin, jenis virus, tingkat keparahan, usia, dan hasil laboratorium. Diperlukan kesiapsiagaan rumah sakit dalam menghadapi fluktuasi pasien COVID-19 dan jumlah permintaan tempat perawatan selama pandemi berlangsung.